STUDI PENGARUH METODE PEMBUATAN DAN SUMBER BAHAN BAKU PADA PROSES PRODUKSI KATALIS DARI ZEOLIT ALAM - Widayat, Widayat; Satriadi, H; Roesyadi, Achmad; Rachimoellah, H M (Universitas Diponegoro, 2013)
Abstract Indonesia has the potential for considerable natural zeolites. This natural zeolites, silica deposits typically have amounted to 60%, it also contains components of alumina. Silica and alumina oxide compound that can be used as a catalyst, particularly in the process of dehydration. This research aims to study the influence of the method of manufacture of catalysts in the production process of natural zeolite catalyst. The observed response is the surface area in comparison with silica, alumina and kristalitas. The surface area is measured by the method kristalitas and BET with XRD analysis as well as the composition of the silica-alumina with AAS. The methods used in this research is the process of exchanging ions-development with alcohol and dealuminiation process with hydrochloric acid solution. The raw materials used are natural zeolite from Malang, Lampung Province and Regency of Gunung Kidul. The results showed that dealuminasi process with hydrochloric acid produces a better surface area compared to the ion exchange process and development with alcohol. Besides the resulting catalyst with silicate dealuminasi process is a catalyst if the raw material of the Regency of Gunung Kidul and mordenite type if the raw materials used originate from Malang. Key words : Zeolite catalyst, natural zeolites, surface area, crystallite,Si/Al comparison